The Implementation Of the Contract Financing Sharia Card PT. Bank Danamon of the Lawof h is Reviewed From the Perspective of Fiqh Muamalah - Aliman Syahuri Zein; Safrul Daulay (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2021)
Abstract Research this aims to know the implementation of the contract financing sharia card on PT. Bank Danamon Syariah if viewed from the perspective of fiqh muamalah. The research is concluded that: 1) Dirham Card launched by referring to the National Sharia Board fatwa Majelis Ulama Indonesia (DSN-MUI) No. 54/DSN-MUI/IX/2006 and a Letter Circular of Bank Indonesia No. 9/183/DPbS/2007 on the approval of Danamon Syariah Card. 2) in the implementation Dirham card using akad Ijarah, so that the holder of the card charged membership fees (the cost of membership); akad Kafalah, cause the issuer of the card can receive a fee (ujrah kafalah); and the contract of Qard, cause the holder of the card is obliged to return by the amount of funds withdrawn in time. 3), some of the provisions about the fee that is required for prospective holder Dirham card, namely the determination of the amounts of the fines and the presence of kvisions and btops (Dhawabith wa hudud). 4), there are some provisions fikih muamalah are not yet clear on the application Dirham Card, namely: (a) the presence of inconsistency in the use of the term on the fatwa of Islamic Card, the term that is used is the contract of Qard but on the provisions of the merchant fee , there are ujrah billing or tahsil al-dayn, on one side using the term Qard, while here. other uses of the term dayn; (b) card credit sharia there is no system of control which can make sure whether the holder of the card using the card 's credit to spend your items are halal course or vice versa; (c) card credit sharia ideally should be able to ensure users do not Israaf (consumptive/excessive), while in the side of another card credit tend to make the holder to be consumptive. In case this is clearly contrary to the principles of shariah; (d) the presence of charge i.e. late charge/fine and there ta'wid (replace loss) which is caused because of a delay in payment. It is certainly going to bring up the question of whether differences in the underlying fine in Sharia Card and Card Credit Conventional.